Kinetic and Mechanistic Studies on the Oxidation of Benzaldehyde with Piperazinium Dichromate in Aqueous Acetic Acid Solution - KANNAPPAN, V.; PARAMESHWARI, K. (Asian Journal of Chemistry, 2010)
This paper contains the results obtained in the detailed kinetic investigations on the oxidation of benzaldehyde by piperazinium dichromate (PZD) in 50 % aqueous acetic acid (v/v) solution. The order in substrate, order in oxidant are established by integral and differential methods. The influence of [HClO4], temperature and addition of neutral salt on the kinetics of this reaction are studied. The activation parameters (ΔH#, ΔS# and ΔG#) are determined accurately for this reaction from the effect of temperature on the rate constant. On the basis of kinetic evidence and product analysis, a suitable mechanism has been proposed.